A promising electrode material modified by Nb-doped TiO2 nanotubes for electrochemical degradation of AR 73. (April 2017) - Xu, Li; Liang, Gaorui; Yin, Ming
Abstract: A distinctive SnO2 Sb electrode with highly ordered Nb doped TiO2 nanotubes sheet as a new substrate, obtained by NbTi alloy anodization, is prepared by pulse electrochemical deposition for the first time as electrocatalytic oxidation anode for wastewater treatment. The novel electrode has a larger surface area and smaller crystallite particles than conventional SnO2 Sb electrodes as obtained from the analysis of scanning electron microscopy and X-ray diffraction. Compared with Ti/SnO2 Sb and Ti/TiO2 -NTs/SnO2 Sb prepared by pulse electrochemical deposition, the electrode modified by NbTiO2 -NTs has the higher oxygen evolution potential of 2.29 V (vs. Ag/AgCl), and the lower charge transfer resistance, which decreased by 65% and 79%. The service lifetime of NbTi/NbTiO2 -NTs/SnO2 Sb is 4.9 times longer than that of Ti/SnO2 Sb and 1.9 times longer than that of Ti/TiO2 -NTs/SnO2 Sb. The new electrode is proved to have an excellent electrochemical oxidation and degradation ability using Acid Red 73 as a target organic pollutant. The AR 73 removal, chemical oxygen demand removal and kinetic rate constant are increased obviously due to the introduction of NbTiO2 -NTs. Besides, the energy consumption reduces 37.2% and 31.4% in contrast with Ti/SnO2 Sb and Ti/TiO2 -NTs/SnO2 Sb. Hence, the Ti/SnO2 Sb modified by NbTiO2 -NTs is a very promising anode material for the electrochemical treatment of dye wastewater. Highlights: The new substrate is of highly ordered Nb doped TiO2 nanotubes array formed by NbTi alloy anodization. A novel SnO2 Sb electrode was successfully prepared by pulse electrochemical deposition. The novel electrode exhibited excellent electrochemical performance, electro-catalytic oxidation ability and stability. The energy consumption was decreased obviously owing to the good conductivity and high electro-catalytic efficiency.